Factors influencing the use of treated wastewater for irrigation in the agricultural sector: Evidence from Iran - Moslem Savari; Mohammad Shokati Amghani; Ashraf Malekian (Cleaner Engineering and Technology)
In recent years, excessive use of freshwater and untreated wastewater for agricultural irrigation has exerted increasing pressure on environmental and natural resources. Hence, this study aimed to identify the influencing factors on Iranian farmers' intention to use Treated Wastewater (TWW) for irrigation in the agricultural sector. The research framework combines two theories: the Theory of Planned Behavior (TPB) and the Technology Acceptance Model (TAM). The study employed a survey method using a questionnaire and structural equation modeling (SEM) for analysis. The statistical population consisted of all irrigated farmers in Tehran Province, the capital of Iran. The results indicate that the integration of TPB and TAM can provide new insights for policymakers aiming to encourage farmers to utilize TWW for agricultural irrigation, thereby promoting environmental sustainability and healthy crop production. The developed framework is capable of explaining 68.1% of the variance in farmers' intention to use TWW. Additionally, the findings reveal that the research variables explain 59.8% and 31% of the variance in the variables perceived usefulness and farmers' attitudes, respectively. In this study, PBC and SN play the most significant roles in the adoption of TWW among farmers. Consequently, policymakers can promote safe practices in the agricultural environment by emphasizing these factors, thereby reducing the excessive consumption of freshwater resources.